The multifaceted challenges faced by women in the field of inherited metabolic disorders - Livia Lenzini; Sara Bianconi; Giorgia Gugelmo; Vincenza Gragnaniello; Simone Messerotti Benvenuti; Gian Paolo Fadini; Nicola Vitturi (Orphanet Journal of Rare Diseases)
Abstract Inherited metabolic disorders (IMDs) are heritable conditions that affect up to 125:100,000 people worldwide. In addition to severe disabling forms that require continuous and costly assistance in both pediatric and adult patients, some IMDs can have mild forms, with the first clinical signs starting in adolescence or very late in adulthood. In the complex field of IMDs, featuring multifaceted challenges that span from scientific discoveries to patient care, women play a central role in contributing to clinical practice, research, patient advocacy, care, and education. In this narrative review, we focused on the involvement of women in the field of IMDs, highlighting not only their extensive contributions but also the undervaluation of the psychological and emotional tolls paid by women dealing with these diseases. Moreover, from a female-centered perspective, we explored the condition of an adult patient with an IMD to highlight the importance of changing the current approach to the clinical management of these diseases toward a more gender-focused approach.